Reconstruction of cranial cruciate ligament in rabbits using polyester implants saturated with PRP, antlerogenic stem cells MIC-1 and their homogenate. (3rd September 2017) - Prządka, Przemysław; Kiełbowicz, Zdzisław; Osiński, Bogdan; Dzimira, Stanisław; Madej, Janusz A.; Nowacki, Wojciech; Kubiak, Krzysztof; Reichert, Paweł; Cegielski, Marek
ABSTRACT: Aim of the study: The attempt to limit the negative effects of polyester implants on the articular cavity by using preparations containing growth factors. Materials and Methods: Polyester implants used for the reconstruction of a rabbit's cranial cruciate ligament (CCL) were saturated with autogenic platelet-rich plasma (PRP), antlerogenic stem cells MIC-1 and their homogenate prior to the surgery. Six months after CCL reconstruction, morphological, and biochemical blood tests were carried out, including proteinogram and acute phase proteins. The knee joints were also examined macro- and microscopically. Results: The results, compared to the control group, showed a favorable effect of the PRP and homogenate of antlerogenic cells on limiting the inflammation caused by the presence of polyester implant in the knee joint. The addition of growth factors caused covering the implant faster with the recipient's connective tissue, thus contributing to reducing the inflammatory reaction of the articular capsule to the presence of polyester. At the same time, no enhanced local or general reaction of the rabbit organism was observed to the presence of xenogenic antlerogenic stem cells MIC-1 homogenate which, like the PRP, may provide an easily available source of growth factors, increasingly often used in regenerative medicine. Conclusions: Applying antlerogenic stem cells, their homogenate or PRP increases the volume of connective tissue that surrounds and intertwines polyester CCL implant, separating it from synovial cavity environment.